Price stability, inflation convergence and diversity in EMU: Does one size fit all? - Axel A. Weber; Günter W. Beck (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
Using a unique data set of regional inflation rates we are examining the extent and dynamics of inflation dispersion in major EMU countries before and after the introduction of the euro. For both periods, we find strong evidence in favor of mean reversion (?-convergence) in inflation rates. However, half-lives to convergence are considerable and seem to have increased after 1999. The results indicate that the convergence process is nonlinear in the sense that its speed becomes smaller the further convergence has proceeded. An examination of the dynamics of overall inflation dispersion (?-convergence) shows that there has been a decline in dispersion in the first half of the 1990s. For the second half of the 1990s, no further decline can be observed. At the end of the sample period, dispersion has even increased. The existence of large persistence in European inflation rates is confirmed when distribution dynamics methodology is applied. At the end of the paper we present evidence for the sustainability of the ECB's inflation target of an EMU-wide average inflation rate of less than but close to 2%.
urn:nbn:de:hebis:30-23427
Keywords: E31; E52; E58; 330; Inflation Convergence; Deflation; ECB Monetary Policy; EMU; Regional Diversity